The influence of sintering temperature to the structural and densification of silica doped zinc oxide for varistor application - Mohamed, Ruziana; Abdul Rasul, Nur Farhaim; Yahya, Norihan; Mamat, Hafiz; Malek, Mohd Firdaus; Ismail, Ahmad Syakirin; Mohd Yusoff, Marmeezee; Senawi, Syamsyir Akmal; Rusop, Mohamad (AIP Publishing, 2019)
The Si doped ZnO nanopowders for varistor have been prepared at different sintering temperature using solid state method. The Si doped ZnO have been sintered at different temperatures 850, 950 and 1050 °C at air condition. The structural and densification of Si doped ZnO were determined using scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis and digital density meter. It was found that the average grain size of Si doped ZnO varistor were 0.81, 1.05 and 2.10µm when sintered at 850, 950 and 1050 °C, respectively. The density of Si doped ZnO were 3.999, 4.453 and 5.332 g/cm when the sintering temperature increased from 850, 950 and 1050 °C, respectively. The density and average grain size of the Si-Doped ZnO is increased with increase of sintering temperature. The Si doped ZnO varistor at different sintering process are polycrystalline structure. It is revealed that the sintering temperature can influence the properties of Si doped ZnO ceramics which is suitable to be used in varistor application.